A STUDY ON WORKING ENVIRONMENT INFLUENCING EMPLOYEE RETENTION OF INDIAN IT PROFESSIONALS - Gangwani, Dr. Sanjeevni; Dubey, Ms. Khushbu (IJRDO - Journal of Applied Management Science, 2016)
In today’s competitive scenario, as the awareness and technology play a vital role indeveloping the competition more essential and intense. Retention becomes one of the biggestissues for the IT industry of India because people are the one who generates profits andconsidered as the capital or asset of the organization. Employee retention is most decisiveconcern facing business leaders as a result of the shortage of skilled labour, economic growthand employee turnover. Retention is defined as “the ability to hold onto those employees youwant to keep, for longer than your competitorsIn modern times, employee’s retention has become one of the leading challenges fororganization. Given today’s weak company loyalty, employees are increasingly "jumpingship" for better job opportunities elsewhere. The issue isn't simply losing a key member ofyour team; there is also the hassle-and cost-of replacement. It is obvious that employee’sretention is one of the most pressing issues that Human Resource Professionals face today.This research paper aims to examine the impact of working environment on employeeretention in IT sector